New-Competitive- Principal of Tumor Control by Low Dose Radiation - A. N. Shoutko; L. E. Yurkova; K. S. Borodulya; L. P. Ekimova (New Frontiers in Medicine and Medical Research Vol. 12, 2021)
In order to verify the principle of indirect control a tumor on the base of morphogenic cells distraction from it, the 114 patients with advanced ovarian carcinoma (stage III-56, stage IY-21, relapse 37), were treated with subtotal half-body (low part) irradiation at low doses (0,1 Gy x 10 for 3 weeks or 3Gy x 3 daily), and obtained data were compared with that for 190 patients (stage III-66, stage IY-25, relapse-99) received conventional local irradiation of the tumor (2 Gy x 23 daily). The surgery and chemotherapy components were equalized in both groups. The 34% and 11% of 5-years survival was obtained at low dose half body irradiation for primary and relapsed patients in comparison with conventional local radiotherapy (7% and 0%). It is concluded, that reparation /regeneration processes being provoked artificially in normal tissues of cancer host are capable to compete remotely with tumor for the morphogenic/feeding cells originated from bone marrow and circulating with the blood.